Changes in microtubule-associated protein tau during peripheral nerve injury and regeneration - Guang-bin Zha; Mi Shen; Xiao-song Gu; Sheng Yi (Neural Regeneration Research, 2016)
Tau, a primary component of microtubule-associated protein, promotes microtubule assembly and/or disassembly and maintains the stability of the microtubule structure. Although the importance of tau in neurodegenerative diseases has been well demonstrated, whether tau is involved in peripheral nerve regeneration remains unknown. In the current study, we obtained sciatic nerve tissue from adult rats 0, 1, 4, 7, and 14 days after sciatic nerve crush and examined tau mRNA and protein expression levels and the location of tau in the sciatic nerve following peripheral nerve injury. The results from our quantitative reverse transcription polymerase chain reaction analysis showed that compared with the uninjured control sciatic nerve, mRNA expression levels for both tau and tau tubulin kinase 1, a serine/threonine kinase that regulates tau phosphorylation, were decreased following peripheral nerve injury. Our western blot assay results suggested that the protein expression levels of tau and phosphorylated tau initially decreased 1 day post nerve injury but then gradually increased. The results of our immunohistochemical labeling showed that the location of tau protein was not altered by nerve injury. Thus, these results showed that the expression of tau was changed following sciatic nerve crush, suggesting that tau may be involved in peripheral nerve repair and regeneration.